INFLASI DAN RETURN ON ASSETS TERHADAP PENYALURAN KREDIT PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zelsy Tamia; Laynita Sari (LPPM Universitas Bina Bangsa, 2024)
This study aims to test whether the Effect of Inflation and Return On Assets on Credit Distribution in Banking companies listed on the Indonesia Stock Exchange in 2019-2022. This type of research used is a quantitative method. The samples used were 45 companies. The technique used is purposive sampling. In analyzing the data using Eviews 10 software. The data analysis method used is panel data regression. Based on the results of the study, it shows that inflation has a positive effect on lending and return on assets has no effect on credit distribution